Sistemas agroindustriais integrados: uma análise por meio da entropia de informação - PONTE, Marcos Ximenes (2012)
Using the mathematical theory of the information, this article analyzes four agroindustry systems of bioenergy production: the industry of alcohol from sugar-cane in Brazil, the industry of corn alcohol and the industry of biodiesel in United States, besides the industry of manioc flour from the Amazonian. Based on an important group of empiric information, evaluations of energy efficiency for different organization levels of the systems are made.